BEING IN EFRAÍN MIRANDA - Llano, Aymara (2008)
The present work is aimed at examining the position of the lyric subject in the collectionof poems Choza by Efrafn Miranda Luján. Our readíng díscerns a controversia! discoursewith regard to white culture since it prompts a reversa! in relation to traditionalhegemonic discourse: in these poems the cultural Other is the White. The subjectmasterly handles the conceptual moulds that Western culture has constructed in arderto characterise the American Indian at the same time a profound skill at writing inSpanish is demonstrated. It is from this perspective that the non-conformist discourseis constituted.